PENGGUNAAN APLIKASI AKUNTANSI BERBASIS EXCEL UNTUK UMKM SECARA DARING - Herliawan, Aditya; Firdaus, Mohamad (CV. Denasya Smart Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an important sector in Indonesia's economy. However, many MSME actors still face challenges in managing financial reports in a simple and effective manner. One solution is to utilize an accounting application based on Microsoft Excel, which is easy to operate and requires no additional costs. This community service activity aims to provide training and mentoring for MSME actors in using Excel-based accounting applications to record transactions, prepare simple financial statements, and monitor the financial condition of their businesses. The implementation of this activity was carried out online through Zoom Meetings and WhatsApp Groups. The methods used included socialization, interactive online training, and online mentoring. The results of the activity showed that participants were able to understand the basic concepts of accounting records and were capable of using a simple Excel application to record daily transactions, prepare income statements, and cash flow reports. This activity is expected to improve financial literacy and the independence of MSME actors in managing their business finances